THE IMPACT OF OFFSHORING ON THE EUROPEAN LABOUR MARKET - Kraciuk, Jakub (Acta Scientiarum Polonorum. Oeconomia, 2017)
This study shows the differences in wages of workers from the EU countries according to various levels of education. It also shows the level of offshoring in the analysed countries and its impact on the salaries. It was found that the largest wage gap between the high-skilled and the low-skilled workers exists both in the countries of Central and Eastern Europe and in the countries such as Germany and Portugal. Results of the analysis show that offshoring contributes to a decrease in wages of workers in the countries of the European Union. Nonetheless, the highest decrease in wages is visible among workers with the lowest skills, and the lowest decrease can be seen among workers with the highest skills.